PENGAWASAN PERIZINAN DEPOT AIR MINUM DI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Mardian Saputra; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Drinking Water Refill Depot business is present in the community as a small industry effort in fulfilling daily drinking water needs. The drinking water depot in its management utilizes technology to streamline the time to meet drinking water needs. The industry of drinking water depots is widespread, with water quality and location and service vary. To meet the quality of drinkable water, the owner of the drinking water depot must meet the business licensing requirements as set forth in Kepmenperindag No. 651 / MPP / Kep / 2004. However, in its development in Kecamatan Singingi Hilir still found drinking water depots that do not have a commercial license or a sign of Industrial List in its operation. Therefore, we need to supervise the business requirements.In this study, referring to the supervision theory proposed by Brantas (2009). The research method used qualitative descriptive method with data collection techniques include observation, interview, study documentation related to research objectives. Sources and types of data in this study consisted of primary and secondary data. Primary data were obtained through interviews with research informants consisting of employees of Dinas Kesehatan and Dinas Koperasi, Small, Medium Enterprises, Trade and Industry of Kuansing Regency, as well as with the owner or employee of drinking water depot business.The results show that the monitoring of permits for drinking water depots has not been running optimally, where the assessment and improvement actions are more focused on the applicant for drinking water depots and periodic limited inspection of the drinking water depots located on the main road in Kecamatan Singingi Hilir, has not been done thoroughly. The influencing factors include, the ability of the supervisory executive, the lack of coordination between the related agencies, and the limited operational budget of supervision.Keywords: Supervision, Coordination, Drinking Water Depot.